Formation Constants of Metal Complexes of Cu(II) and Dy(III) with N-Substituted Anthranilic Acids in Different Aquo-Organic Solvents - Krishna Rao, B.; Laxmi, K.; Sarala Devi, Ch. (Asian Journal of Chemistry, 2010)
The formation constants of Cu(II) and Dy(III) with Nsubstituted anthranilic acids have been determined potentiometrically by varying proportions of dioxane-water, acetonewater, isopropanol-water and ethanol-water at 30 ºC and 0.1 M ionic strength. The results are discussed with reference to the change in dielectric constant of water in the presence of organic solvent, change in structure and hydrogen bonding in water, relative solvent basicity and proton solvation by the organic solvent.